Quản lí bảo đảm chất lượng trường tiểu học, trung học cơ sở theo mô hình chính quyền địa phương hai cấp: Nghiên cứu lí luận và đề xuất cơ chế quản lí - Phan, Hồng Dương (Tạp chí Giáo dục, 2026)
In the context of educational management innovation, the need for decentralization and delegation of power in state management and the trend of international integration has become critical. The article analyzes the theoretical and practical basis and proposes orientations for building a management mechanism that adapts to the current context of educational management innovation in Vietnam. The results show that quality assurance management in the two-level local government model requires a clear division of roles between the stakeholders: the Department of Education and Training takes on the core role in directing, inspecting and supervising; the People's Committee at the commune level directly manages and at the same time engages the community in implementation; and the school promotes autonomy, proactively implements quality assurance activities and is responsible for explaining the results. Practice also shows that many challenges arise when there is no longer an intermediate level, especially in terms of resources, management capacity and coordination mechanisms. From that basis, the study proposes a quality assurance management mechanism in the direction of establishing unified orientations and principles, clearly defining the responsibilities of each entity, and at the same time establishing a close coordination mechanism and necessary conditions to ensure implementation.